Effects of Sleeve Gastrectomy on Fecal Gut Microbiota and Short-Chain Fatty Acid Content in a Rat Model of Polycystic Ovary Syndrome - Lin, Wei; Wen, Lingying; Wen, Junping; Xiang, Guangda (Frontiers in Endocrinology, 2021)
Purpose: Sleeve gastrectomy (SG) is a surgical intervention for polycystic ovary syndrome (PCOS), especially for patients with obesity. Here, we explored the effects of SG on the gut microbiota of rats with PCOS and investigated the association between the intestinal flora and efficacy of SG in PCOS. Methods: Dehydroepiandrosterone (DHEA) injection was administered alone and in combination with a high-fat diet to induce PCOS in rats. SG was performed in rats with PCOS, and the effects of SG on the fecal and gut microbiota and the short-chain fatty acid (SCFA) content were observed. Furthermore, the association among gut microbiota, SCFA content and hyperandrogenism or other hallmarks of PCOS was evaluated. Results: The abundance of Firmicutes reduced and that of Bacteroidetes increased in response to SG in the DHEA-induced PCOS rat model. At the genus level, the abundances of Bacteroides and Blautia increased and those of Ruminococcus, Clostridium, and Alistipes reduced distinctly in the PCOS-SG groups. Moreover, the levels of fecal SCFAs, especially butyric acid, reduced after SG. SG significantly ameliorated PCOS-related symptoms such as hyperandrogenism, disrupted ovary function, and impaired glucose tolerance. Bacteroides and Blautia exhibited a negative correlation and Ruminococcus, Clostridium, and Alistipes exhibited a positive correlation with the levels of fecal SCFAs, luteinizing hormone, testosterone, and inflammatory factors. Conclusions: The amelioration of PCOS-related reproductive and metabolic disorders following SG was associated with the regulation of microbial taxa and SCFA content. Our findings provide a novel perspective on the microbial mechanisms in PCOS after SG.